2011
DOI: 10.15288/jsad.2011.72.390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Premature Birth on the Risk for Alcoholism Appear to Be Greater in Males Than Females

Abstract: ABSTRACT. Objective: A large Danish birth cohort was used to test the independent and joint effects of perinatal measures associated with premature birth as predictors of the development of alcoholism in male and female subjects. Method: Subjects were born at the Copenhagen University Hospital between 1959 and 1961 (N = 9,125). A comprehensive series of measures was obtained for each of the 8,109 surviving and eligible infants before birth, during birth, shortly after birth, and at 1 year. The adult alcoholism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
6
1
1
Order By: Relevance
“…Unlike a study conducted by Manzardo, Madarasz, & Gabrielli (2011) demonstrating a significantly greater degree of prematurity among subjects who would later develop alcoholism, this study found no significant association between GA and alcohol dependence. That sample included 8,109 eligible subjects born at the Copenhagen University Hospital between 1959 and 1961, 448 (5.5%) of which received a formal diagnosis of alcohol at some point in their lifetime (Manzardo, Madarasz & Gabrielli 2011).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike a study conducted by Manzardo, Madarasz, & Gabrielli (2011) demonstrating a significantly greater degree of prematurity among subjects who would later develop alcoholism, this study found no significant association between GA and alcohol dependence. That sample included 8,109 eligible subjects born at the Copenhagen University Hospital between 1959 and 1961, 448 (5.5%) of which received a formal diagnosis of alcohol at some point in their lifetime (Manzardo, Madarasz & Gabrielli 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…That sample included 8,109 eligible subjects born at the Copenhagen University Hospital between 1959 and 1961, 448 (5.5%) of which received a formal diagnosis of alcohol at some point in their lifetime (Manzardo, Madarasz & Gabrielli 2011). One potential explanation for this could be that the Manzardo et al (2011) study considered the development of alcoholism by age 45-47 years (in 2007), while ours was restricted to age 18 years. Overall, less than 1% of our entire sample of UK 18-year olds met DSM-IV-TR criteria for alcohol dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The compulsive use of alcohol and other substances arises from genetic, neurobiological and developmental, environmental and psychosocial influences that direct both the likelihood (and level) of alcohol exposure as well as biologic response (Knop et al, 2003; Manzardo et al, 2005; 2006; 2011; Spanagel, 2009; Schuckit, 2009b; Yan et al, 2013). Genetic factors are particularly important and contribute an estimated 40% to 60% of the risk of developing alcoholism (Goodwin et al, 1974; Prescott and Kendler, 1999; Schuckit, 2009b; Yan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A LCOHOLISM IS A chronic, severe relapsing disorder with global impact on individuals and society contributing to significant illness, injury, and death worldwide each year (Schuckit, 2009a;Whiteford et al, 2010). The compulsive use of alcohol and other substances arises from genetic, neurobiological and developmental, environmental, and psychosocial influences that direct both the likelihood (and level) of alcohol exposure and biologic response (Knop et al, 2003;Manzardo and Penick, 2006;Manzardo et al, 2005Manzardo et al, , 2011Schuckit, 2009b;Spanagel, 2009;Yan et al, 2013). Genetic factors are particularly important and contribute an estimated 40 to 60% of the risk of developing alcoholism (Goodwin et al, 1974;Prescott and Kendler, 1999;Schuckit, 2009b; Yan et al, 2013).…”
mentioning
confidence: 99%
“…O álcool pode levar à hipóxia fetal causando CIUR e aumento do número de vasos cerebrais, porém com lúmen reduzido. 12 (B) Além disso, a prematuridade é considerada importante consequência da Síndrome Alcoólica Fetal 8,11 (B). No entanto, em um estudo de coorte (B), o álcool foi associado a menor número de nascimentos pré-termo, mas como parcela da população estudada consumia outras drogas como a maconha e cocaína, este fato pode ter influenciado esse resultado.…”
unclassified